PEMBELAJARAN KEWIRAUSAHAAN MELALUI KUNJUNGAN USAHA: STUDI KASUS PADA PANGKALAN LPG ALUMNI - Hafidz Ainur Rofi; Thoyib Ramadhan; Faricha Noor Aida (Media Resonansi Pengabdian Masyarakat, 2025)
This community service activity aims to analyze the dynamics of LPG tube base micro businesses managed by alumni of the entrepreneurship study program. Through business visits and in-depth interviews, this research identifies operational aspects, challenges, and strategies implemented in the LPG distribution business. The findings of the study highlight the importance of effective financial management, adaptation to government regulations, and understanding of market dynamics in achieving business sustainability.Keywords : Micro business, LPG cylinder base, Entrepreneurship, Business challenges, Financial management